"weil – das ist eben doch richtig so" Teaching variant types of weil‐ and obwohl‐structures in German1. Issue 2 (September 2016) - Bendig, Ina; Betz, Emma; Huth, Thorsten
Abstract : Researchers have observed that in spoken German, the conjunctions weil and obwohl commonly occur with verb‐second ( V 2) instead of verb‐final (Vf ) word order (Gaumann, 1983 ; Gänthner, 1993, 1996 ; Uhmann, 1998 ). Current findings document that this syntactic variant of weil/obwohl‐structures has an alternative interactional meaning and function, namely expressing different causalities (Vandergriff, 2005 ). Based on the results of interactional linguistic research, we will outline why it is important for foreign language learners of German to be aware of the weil/obwohl +V 2 structure. This background provides the basis for step‐by‐step teaching units on variant weil/obwohl ‐clauses in the beginning and intermediate German language classroom. The suggested teaching units employ the five phases for teaching and learning pragmatics suggested by Barraja‐Rohan (1997 ). The aim is to raise learners' awareness and understanding for this syntactic phenomenon and its interactional use in spoken German.